Tugas, Fungsi dan Bagian Sekretariat DPRD dalam Membantu Tugas Anggota Dewan Perwakilan Rakyat Daerah (DPRD) Kota Palangka Raya - Muhammad Kurniawan; Salsabila Salsabila; Novi Lidiyasari (Nusantara Mengabdi Kepada Negeri, 2025)
This research aims to understand the functions and duties of the Secretariat of the Regional People's Representative Council (DPRD) in assisting council members in carrying out their duties. According to the Mayor Regulation Number 34 of 2019, the Secretariat of the DPRD of Palangkaraya City consists of the following divisions: Secretary, General Affairs, Legislation Affairs, Sessions, Public Relations, and Budgeting and Supervision Facilities. Based on Law No. 32 of 2004 and Government Regulation No. 41 of 2007, the Secretariat of the DPRD is considered a "regional apparatus" that provides "administrative services" to the DPRD. This includes managing the DPRD's financial administration, supporting the duties and functions of the DPRD, and providing and coordinating the necessary experts for the DPRD. As explained earlier, the Secretariat of the DPRD plays a crucial and vital role in determining the effectiveness of the DPRD's services. Based on the research objectives outlined, the research method suitable for understanding the functions and duties of the Secretariat of the DPRD in assisting council members is a descriptive method with a qualitative approach. This approach will allow the researcher to describe and analyze the empirical reality in-depth regarding the role of the Secretariat of the DPRD.